Understanding gender-roles behavior in South East Asia’s (SEA) developing nations / Khairul Azfar Adzahar, Masilah MOhamad and Mohd Shafiz Saharan - Adzahar, Khairul Azfar; Mohamad, Masilah; Saharan, Mohd Shafiz (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2020)
Although women in South East Asia have undergone enormous socio-economic changes in the last few decades; most nations are still struggling to position women as an active decision-maker both in home and at work. This is mainly due to the traditional patriarchal behaviour and women’s lack of access to financial sources (Daniell, 2012). Apart from that, a stereotypical masculine workplace also creates a false dichotomy of what women can and cannot do; such as holding a leadership position. The known cause for this alarming socio-economic imbalance between man and women and attitudes to gender-roles behaviour in South East Asia are mainly due to the discerning social norms and culture.